Post-Induction Management in Patients With Left-Sided RAS and BRAF Wild-Type Metastatic Colorectal Cancer Treated With First-Line Anti-EGFR-Based Doublet Regimens: A Multicentre Study - Parisi, Alessandro; Cortellini, Alessio; Venditti, Olga; Filippi, Roberto; Salvatore, Lisa; Tortora, Giampaolo; Ghidini, Michele; Nigro, Olga; Gelsomino, Fabio; Zurlo, Ina Valeria; Fulgenzi, Claudia; Lombardi, Pasquale; et al. (Frontiers in Oncology, 2021)
Background: Few data regarding post-induction management following first-line anti-EGFR-based doublet regimens in patients with left-sided RAS/BRAF wild-type metastatic colorectal cancer (mCRC) are available. Methods: This multicentre, retrospective study aims at evaluating clinicians’ attitude, safety and effectiveness of post-induction strategies in consecutive patients affected by left-sided RAS/BRAF wild-type mCRC treated with doublet chemotherapy plus anti-EGFR as first-line regimen, who did not experience disease progression within 6 months from induction initiation, at 21 Italian and 1 Spanish Institutions. The measured clinical outcomes were: PFS, OS, adverse events, ORR. Results: At the data cut-off, among 686 consecutive patients with left-sided RAS/BRAF wild-type mCRC treated with doublet plus anti-EGFR as first-line regimen from March 2012 to October 2020, 355 eligible patients have been included in the present analysis. Among these, 118 (33.2%), 66 (18.6%), and 11 (3.1%) received a maintenance with 5FU/LV+anti-EGFR, anti-EGFR, and 5FU/LV, respectively, while 160 (45.1%) patients continued induction treatment (non-maintenance) until disease progression, unacceptable toxicity, patient decision or completion of planned treatment. The median period of follow-up for the overall population was 33.7 months (95%CI: 28.9-35.6). Median PFS of the 5FU/LV+anti-EGFR, anti-EGFR, 5FU/LV, and non-maintenance cohorts was 16.0 (95%CI: 14.3-17.7; 86 events), 13.0 (95%CI: 11.4-14.5; 56 events), 14.0 (95%CI: 8.1-20.0; 8 events), and 10.1 months (95%CI: 9.0-11.2; 136 events), respectively (p<0.001). Median OS was 39.6 (95%CI: 31.5-47.7; 43 events), 36.1 (95%CI: 31.6-40.7; 36 events), 39.5 (95%CI: 28.2-50.8; 4 events), and 25.1 months (95%CI: 22.6-27.6; 99 events), respectively (p<0.001). After adjusting for key covariates, a statistically significant improvement in PFS in favor of 5FU/LV+anti-EGFR (HR=0.59 [95%CI: 0.44–0.77]; p<0.001) and anti-EGFR (HR=0.71 [95%CI: 0.51–0.98]; p=0.039) compared to the non-maintenance cohort, was found. Compared to the non-maintenance cohort, OS was improved by 5FU/LV+anti-EGFR (HR=0.55 [95%CI: 0.38–0.81]; p=0.002) and, with marginal significance, by anti-EGFR (HR=0.67 [95%CI: 0.51–0.98]; p=0.051). No difference was found in ORR. Any grade non-hematological and hematological were generally higher in the non-maintenance compared to the maintenance cohorts. Conclusion: Among treatment strategies following an anti-EGFR-based doublet first-line induction regimen in patients affected by left-sided RAS/BRAF wild-type mCRC treated in a “real-life” setting, 5FU/LV+anti-EGFR resulted the most adopted, effective and relatively safe regimen.